Penerapan Metode Jarimatika Dalam Meningkatkan Kecepatan Berhitung Pembagian Bilangan 2 Sampai 40 Untuk Siswa Kelas 3 Di SD Negeri 2 Ngering Jogonalan - Suminten, Suminten (Universitas Sebelas Maret, 2022)
The arithmetic operation of division is one of the four basic arithmetic operations which is material that is often taught in elementary schools. to explain division so that students can more easily understand and be skilled in determining the results for him, until now it has been a problem. By conducting the research, it aims to determine the effectiveness of the division of the division technique between numbers 2 to 40 which is expected to increase student achievement and make it easier for teachers to convey material distribution in order to create a fun learning atmosphere. The method used in this research is Classroom Action Research (CAR), which consists of two cycles. Each cycle includes planning, implementation, observation and reflection. Data collected through posttest in each cycle and questionnaires. The results showed that the effort to increase the speed of calculating the division of numbers from 2 to 40 by applying the jarimatics method was carried out by dividing the class action into 2 cycles. The fastest time for cycle 1 is 52 seconds to work on one division problem. The average time to complete one multiplication problem is 47.63 seconds. The fastest time in cycle 2 is 8 minutes or 32 seconds to complete 15 items about dividing numbers 2 to 40. In cycle 2 the average value increases to 83.45 and all students have reached the KKM limit of 70.